Safety and tolerability of moxifloxacin in the treatment of respiratory tract infections: a post-marketing surveillance conducted in Indonesia (Medical Journal of Indonesia, 2005)
Moxifloxacin 400 mg tablet has been marketed in Indonesia for several indications, i.e. acute exacerbation of chronic bronchitis (AECB), community-acquired pneumonia (CAP), and acute bacterial sinusitis (ABS). To assess the safety and tolerability of moxifloxacin, a post-marketing surveillance study was conducted in the year 2001 involving 589 physicians. Clinical efficacy was also evaluated, both by physicians and patients, using a 6-symptom total score, which was scaled 0-12. A total of 1715 patients with acute sinusitis, CAP, AECB, and other infections were treated with oral moxifloxacin 400 mg once daily. There were 151 (8.8%) patients with adverse events (AEs) and 5 (0.29%) patients with serious adverse events (SAEs) that were considered related to moxifloxacin treatment. The most common adverse reactions were nausea (4.96%), dizziness (1.52 %), vomiting (0.64%), headache (0.47%), andweakness (0.47%). Twenty three (1.34%) patients discontinued treatment due to adverse events. Tolerance to treatment was rated very good and good by 647 (37.7%) and 919 (53.6%) of patients, respectively. Based on physicians’ clinical assessment, 57.7% of patients were cured and 39.9% were improved at the end of treatment. Mean total symptom score, as assessed by the patients, decreased from 6.43 on day-1 to 2.76 on day-3. Totally, 95.3% of patients felt better after receiving moxifloxacin and 97.6% of patients had good impression on moxifloxacin treatment. In conclusion, treatment of respiratory tract infections, mainly AECB, CAP and ABS, with moxifloxacin 400 mg once daily in this post-marketing surveillance was shown to be safe and well tolerated. Moxifloxacin was also shown to be highly effective in the treatment of these infections with rapid improvement of symptoms. (Med J Indones 2005; 14: 11-19) Keywords : post-marketing survtillance, PMS, moxifloxacin, respiratory tract infections